Genetically modified mesodermal-derived cells for bone tissue engineering. - Kofron, M.D.
Alternatives to autografts and allografts for accelerated healing of skeletal defects. This article discusses the use of cells, isolated from tissues originating from the mesodermal germ layer and genetically modified to express bone morphogenetic protein, for bone tissue engineering applications.
Keywords: Accelerated healing; Bone morphogenetic protein; Bone tissue engineering; Bone tissue engineering applications; Genetically modified mesodermal-derived cells; Mesodermal germ layer; Skeletal defects